Pengaruh Keberadaan Ruang Publik Tepian Air terhadap Perubahan Nilai Jual Objek Pajak (NJOP) Lahan - Rahayu Pratiwi; Slamet Trisutomo; Mukti Ali (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2017)
The existence of Seruni Beach as one of the Bantaeng Regency icons shows the development of the city element in this case public space, as a form of new activity centers that can trigger the growth of diverse community activities around the coast and an increase in the economic value of the region which has an impact on increasing the number of Tax Objects (OP ) as well as changes to the Tax Object Selling Value (TOSV). This study aims to explain the development of land NJOP before and after the existence of Seruni Beach and determine the effect of the presence of Seruni Beach as a waterfront public space on changes in land NJOP. The method used is descriptive, spatial, network, and regression methods. The results of the analysis show the pattern of development of land NJOP that there is no significant change in land NJOP in 2008-2010, then the increase occurred in 2011 and tends to remain in 2012-2014, then increased in 2015. The proportion of influence of distance, radius and function variables the building as an indicator of the existence of Seruni Beach as a public waterfront is 35.6%. Furthermore, the remaining 64.4% (100% minus 35.6%) is influenced by other variables, in this case variables other than the existence of Seruni Beach. So that, overall, the results of the regression analysis showed that the presence of Seruni Beach did not have a significant influence on NJOP changes, as evidenced by the Sig <0.05 with a proportion of influence of 35.6%. This indicates the existence of Seruni Beach public space has a small correlation (correlation) effect on changes in land NJOP in the study area.